Pencegahan Ujaran Kebencian di Media Sosial Melalui Peringatan Virtual Polisi (PVP) di Bareskrim Polri - Chaniago, Herio Ramadhona; Muhammad Syah, Bakharuddin; Wahyuni, Sari (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2023)
Prevention of Hate Speech on Social Media through Virtual Police Warnings (PVP) at Bareskrim Polri has shown insignificant results. Targeted social media users tend to disobey and ignore warnings, which results in hate speech still being found on social media. Therefore, this study aims to analyze the implementation of PVP at Bareskrim Polri through the Situational Crime Prevention Approach and the Social Prevention Approach. This research also considers the Space Transition Theory and Perceptual Deterrence Theory to analyze the response of social media users through the perspective of members involved in PVP operations. This research method implements qualitative research with a case study approach. In order to obtain in-depth data, researchers applied snowball sampling in the form of in-depth interviews, document studies of work plans, annual reports, SOPs, and regulations related to PVP, and non-participant observation by coming to the control room and observing PVP operations. The research findings include the finding that the prevention of hate speech on social media through PVP belongs to the Situational Crime Prevention Approach, but PVP is not in line with this approach because the education variable is part of Social Crime Prevention. It was found that there are five causes of social media users not complying with and ignoring PVP, namely differences in reality, semianonymity and anonymity, differences in values and norms, buzzer accounts, and perceptions of the absence of sanctions. Despite the weaknesses in PVP, prevention of hate speech crimes on social media can be implemented by applying the Illegal Content Crime Triangle Model. The limitation of this study involves research at Bareskrim Polri; therefore, further studies are needed in other locations to complement this research. For academics, this research enriches police knowledge in preventing hate speech or other illegal content through social media. For practitioners, this research provides comprehensive prevention in addressing hate speech or illegal content on social media in cyberspace.